2013
DOI: 10.1111/joor.12060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the bolus volume on hyoid movements in normal individuals

Abstract: The hyoid bone moves during swallowing due to contraction of suprahyoid muscles, which are critical components of normal swallowing function. It has been reported that the muscle force and shortening velocity decline gradually with age. Reduced hyoid velocities may delay the sealing of the laryngeal vestibule and opening of the cricopharyngeal muscle. We hypothesised that the hyoid velocity could be a factor influencing aspiration. This study evaluated effects of bolus volume changes on the hyoid distance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 21 publications
(26 reference statements)
1
30
0
Order By: Relevance
“…Likewise, faster excursion velocity with increased bolus volume is consistent with prior reports [27,33]. Increased hyoid excursion magnitude and velocity with the larger bolus volume likely reflects the involuntary bolus accommodation process [21] in which the biomechanical aspects of swallowing system adapt to different bolus volumes to maintain optimal functional swallowing.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Likewise, faster excursion velocity with increased bolus volume is consistent with prior reports [27,33]. Increased hyoid excursion magnitude and velocity with the larger bolus volume likely reflects the involuntary bolus accommodation process [21] in which the biomechanical aspects of swallowing system adapt to different bolus volumes to maintain optimal functional swallowing.…”
Section: Discussionsupporting
confidence: 78%
“…While some studies have found comparable excursion magnitudes between the hyoid and larynx during swallowing [14,15], other studies have reported different excursion magnitudes between these structures [16,17]. Hyolaryngeal excursion has been reported to be influenced by both age and bolus characteristics [17][18][19][20][21][22][23][24][25][26][27]. Studies of age-related changes in hyolaryngeal excursion have focused primarily on excursion duration and excursion magnitude.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…superior, anterior). Several recent studies suggest that hyoid velocity may differ between healthy and pathological swallows, with the latter having significantly reduced velocity [5, 8, 1416]. Another parameter of potential clinical relevance is peak hyoid velocity, defined as the maximum rate of position change within a single plane of hyoid movement (Y: superior-inferior; or X: anterior-posterior).…”
Section: Introductionmentioning
confidence: 99%